Petals on the River - Woodiwiss, Kathleen E. (New York Avon Books, 1998)
Falsely convicted of thievery and sent to America on a slave ship, Shemaine O'Hearn beomes the servant of Gage Thornton, a "caring, generous and enigmatic ... shipbuilder with a young child in need of a nanny."
Keywords: Virginia -- Romance fiction